2020
DOI: 10.1093/jhps/hnaa004
|View full text |Cite
|
Sign up to set email alerts
|

Squat and gait biomechanics 6 months following hip arthroscopy for femoroacetabular impingement syndrome

Abstract: The purpose of this study was to (i) assess whether squat and gait biomechanical measures improve in patients with femoroacetabular impingement syndrome (FAIS) 6 months after surgery compared to pre-operative measures and (ii) compare biomechanical properties to controls without FAIS. In this prospective study, biomechanical data during a double leg squat task and gait for 15 FAIS patients and 9 controls were collected using three-dimensional motion analysis. Data were collected in the FAIS group at two-time p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 51 publications
3
19
0
Order By: Relevance
“…The current study adds to previous studies on gait biomechanics before and after surgery for FAIS (7)(8)(9)(10)(11), as well as another study that investigated muscular synergy control of gait in patients with hip pathology (38). Rylander et al reported that patients demonstrated improvement of maximal hip internal rotation and sagittal plane range motion during gait following hip arthroscopic surgery for FAIS (7).…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…The current study adds to previous studies on gait biomechanics before and after surgery for FAIS (7)(8)(9)(10)(11), as well as another study that investigated muscular synergy control of gait in patients with hip pathology (38). Rylander et al reported that patients demonstrated improvement of maximal hip internal rotation and sagittal plane range motion during gait following hip arthroscopic surgery for FAIS (7).…”
Section: Discussionmentioning
confidence: 61%
“…We acknowledge that the sample size of the study is small, however, the longitudinal design evaluating patients at 1-year after hip arthroscopy is valuable because extremely limited data exists in this area (7)(8)(9). Challenges associated with patient attrition, the time burden of marker based motion analysis testing, and limitation in number of high volume hip arthroscopy centers capable of motion analysis testing contributes to the generally small sample sizes and limited number of postoperative biomechanical studies in FAIS and (7)(8)(9)(10)(11). Other studies have attempted to overcome this by including patients undergoing any type of surgery for FAIS (open vs. arthroscopic), ( 9) and have reported on short term outcomes (10,11).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations